Phytochemical Potential of Maggot Extract Antimicrobial for Escherichia Colisp. in Diabetic Ulcers of Diabetes Mellitus II (Jurnal Veteriner dan Biomedis, 2024)
Diabetes Mellitus (DM) is a metabolic disorder related to the relative deficiency of insulin secretion, affecting the metabolism of carbohydrates, fats, and proteins, leading to chronic hyperglycemia caused by genetic and environmental factors. This condition significantly impacts the quality of life, primarily due to complications such as diabetic ulcers. Diabetic foot ulcers are non-traumatic lesions on the skin of the foot in individuals with diabetes mellitus, resulting from repeated pressure and associated diabetes complications related to peripheral neuropathy. The healing of wounds can be facilitated through Maggot Debridement Therapy, a treatment involving the application of maggots or larvae of the Black Soldier Fly (BSF). These maggots secrete enzymes that dissolve necrotic tissue, disinfect the wound, and stimulate wound healing. This study aims to analyze the effectiveness of methanol extract from Maggot (H. illucens) in inhibiting the migration of bacterial cultures and its potential as an antimicrobial agent against bacteria found in diabetic foot ulcers (DM II). The maggot was extracted using the maceration method with methanol, and its content was determined through phytochemical and GC-MS tests. The antibacterial test was conducted using E. coli. Phytochemical testing revealed that the methanol extract of maggot contains saponin, as evidenced by the formation of foam after the addition of distilled water and agitation. The results of the antibacterial test indicated that the methanol extract of Maggot (Hermetia illucens) can inhibit the growth of Escherichia coli bacteria concentration of 12,5%.